Management Process and Human reliability Analysis of In-service Inspection for the Mechanical Components in PWRs. (September 2020) - Li, Tian; Xue, Donglin; Yan, Hai; Yin, Qin
Abstract: Based on the management strategy of in-service inspection, emphatically analysing the human reliability of in-service inspection persons, aimed at improving the management system and raising the management level for in-service inspection for the Mechanical components in PWRs.